2019
DOI: 10.1155/2019/2691808
|View full text |Cite
|
Sign up to set email alerts
|

TLR7 Modulated T Cell Response in the Mesenteric Lymph Node of Schistosoma japonicum-Infected C57BL/6 Mice

Abstract: Toll-like receptors (TLRs) play an important role in regulating immune responses during pathogen infection. However, roles of TLRs on T cells reside in the mesenteric lymph node (MLN) were not be fully elucidated in the course of S. japonicum infection. In this study, T lymphocytes from the mesenteric lymph node (MLN) of S. japonicum-infected mice were isolated and the expression and roles of TLR2, TLR3, TLR4, and TLR7 on both CD4+ and CD8+ T cells were compared. We found that the expression of TLR7 was increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…The results indicated that the relative TLR7 mRNA level in hepatic lymphocytes from infected mice was lower than that in hepatic lymphocytes from naive mice. This might be induced by the amount of infection, recruiting lower TLR7expressing lymphocytes, such as T cells and B cells, as we observed in mesenteric lymph nodes (Qu et al, 2019). This hypertension was validated by the FCM results, which indicated that the percentage of TLR7-expressing cells was increased in the isolated hepatic lymphocytes.…”
Section: Discussionsupporting
confidence: 71%
“…The results indicated that the relative TLR7 mRNA level in hepatic lymphocytes from infected mice was lower than that in hepatic lymphocytes from naive mice. This might be induced by the amount of infection, recruiting lower TLR7expressing lymphocytes, such as T cells and B cells, as we observed in mesenteric lymph nodes (Qu et al, 2019). This hypertension was validated by the FCM results, which indicated that the percentage of TLR7-expressing cells was increased in the isolated hepatic lymphocytes.…”
Section: Discussionsupporting
confidence: 71%
“…SEA and SWA are major antigens to induce liquid immune response in S . japonicum infected mice [ 6 ]. To explore the roles of B cells in the spleens of S .…”
Section: Resultsmentioning
confidence: 99%
“…For example, our previous study found that the percentage of TLR7 expressed T lymphocytes from the mesenteric lymph node (MLN) of S . japonicum infected mice increased on week 6 post infection [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the expression of TLR7 is increased in the mesenteric lymph node CD4 + and CD8 + T cells after Schistosoma japonicum infection. The TLR7 agonist can enhance the production of IFN-γ in CD8 + T cells from mesenteric lymph node T cells in infected mice ( 141 ). Moreover, TLR7/MyD88-dependent signaling activation in CD8 + T cells can promote cellular glycolysis and enhance T cell effector functions ( 142 ).…”
Section: Tlr-mediated Regulation Of T Cellsmentioning
confidence: 99%